Hubungan Stres Akademik dengan Perilaku Cyberloafing pada Mahasiswa - Muhammad Nurul Aziz; Oki Mardiawan (Jurnal Riset Psikologi, 2025)
Abstract. This research aims to determine the relationship between academic stress and cyberloafing behavior among students in the city of Bandung. This research uses a cross-sectional survey. The measuring instruments used in this research are academic stress which was measured using the Student-Life Stress Inventory (SSI) adapted by Pragholapati and cyberloafing which was measured using the cyberloafing scale adapted by Simanjuntak. The sample for this research was 291 student respondents in Bandung City. From the results of confirmatory factor analysis with SEM, the proposed model meets the fit criteria (GFI = 0.935; CFI = 0.954; IFI = 0.954; NFI = 0.908; RMSEA = 0.057). The results of research using the Structural Equation Modeling (SEM) analysis model show that there is a positive relationship between academic stress and cyberloafing behavior in students in Bandung City with a positive significant value of 0.084. This value shows that there is a weak correlation between academic stress and cyberloafing behavior with a positive relationship, so the higher the level of academic stress, the higher the level of cyberloafing among students in Bandung City. Abstrak. Penelitian ini bertujuan untuk mengetahui adanya hubungan antara stres akademik dengan perilaku cyberloafing pada mahasiswa di Kota Bandung. Penelitian ini menggunakan survey dengan cross-sectional. Alat ukur yang digunakan dalam penelitian ini yakni stres akademik yang diukur menggunakan Student-Life Stress Inventory (SSI) yang diadaptasi oleh Pragholapati dan cyberloafing yang diukur mengunakan skala cyberloafing yang diadaptasi oleh Simanjuntak. Sampel penelitian ini sebanyak 291 responden mahasiswa di Kota Bandung. Dari hasil analisis faktor konfirmatori dengan SEM, model yang diajukan memenuhi kriteria fit (GFI = 0,935; CFI = 0,954; IFI = 0,954; NFI = 0.908; RMSEA = 0,057). Hasil penelitian dengan menggunakan model analisis Structural Equation Modeling (SEM) menunjukkan terdapat hubungan yang positif antara stres akademik dengan perilaku cyberloafing pada mahasiswa di Kota Bandung dengan nilai signifikan positif sebesar 0.084. Nilai tersebut menunjukkan adanya korelasi yang lemah antara stres akademik dengan perilaku cyberloafing dengan arah hubungan positif, maka semakin tinggi tingkat stres akademik maka semakin tinggi pula tingkat cyberloafing pada mahasiswa di Kota Bandung.